Designing Scalable CI/CD Pipelines for Regulated Enterprises Using Kubernetes and GitOps - Shashi Kumar Munugoti (International Journal of Computational and Experimental Science and Engineering, 2025)
Legacy software delivery practices pose difficulties in regulated industries such as financial services, healthcare, and government, where organizations must comply with governance requirements throughout the software delivery lifecycle while protecting sensitive information. Most common continuous integration and continuous delivery CI/CD pipelines lack auditability and traceability and include manual processes, which are a bottleneck in the release process to production systems. Environment inconsistencies lead to deployment failures and configuration drift across infrastructure tiers. The article presents an architectural framework combining Kubernetes orchestration with GitOps methodology for regulated enterprise environments. Declarative configuration management establishes Git repositories as authoritative sources for infrastructure state. Pull-based deployment models eliminate direct pipeline access to production clusters. Zero-trust security principles ensure continuous verification of access requests regardless of network origin. Policy-driven automation embeds compliance validation throughout the build and deployment stages. Admission controllers enforce governance rules at deployment time without manual intervention. Comprehensive observability mechanisms provide audit capabilities satisfying regulatory examination requirements. The framework enables organizations to accelerate deployment frequency while preserving rigorous change management controls. Separation of duties occurs naturally through pull request approval workflows. The architectural patterns presented address fundamental gaps in traditional CI/CD implementations for highly regulated operational contexts.